Identifying the patterns of ultra-processed food consumption and their characteristics in the UK adults using the UK National Diet and Nutritional Surveys 2008/09 to 2018/19 - Martino Bussa; Federico Ambrogi; Valeria Edefonti; Martin O’Flaherty; Yanaina Chavez-Ugalde; Zoè Colombet (Public Health Nutrition)
Abstract